The 4Rs of Aquatic Rescue: educating the public about safety and risks of bystander rescue. Issue 3 (3rd July 2017) - Moran, Kevin; Webber, Jonathon; Stanley, Teresa
Abstract : From 1980 to 2014, 87 persons drowned in New Zealand while attempting to rescue others; all incidents occurred in open water and most (80%) fatalities were male. While bystander rescue has been promoted as a way of preventing drowning, little is known about the knowledge base that informs potential rescuers. This study utilized a family water safety programme to promote a resource entitled the 4Rs of Aquatic Rescue. Participants ( n = 174) completed a pre-intervention survey and were then provided with information and access to electronic resources on safe bystander rescue techniques. Most respondents (71%) had never been taught rescue techniques, and males were more confident of their rescue ability. Upon completion of the programme, significant differences were evident in respondents' understanding of rescue safety, but this did not translate to greater confidence or disposition towards performing a rescue. Ways of promoting bystander safety around water are discussed and recommendations for future studies are made.